Dose-reduced fludarabine, cyclophosphamide and rituximab is well tolerated in older patients with chronic lymphocytic leukemia and has preserved therapeutic efficacy. Issue 5 (3rd May 2016) - Lew, Thomas E.; Cheah, Chan Y.; Carney, Dennis A.; Prince, H. Miles; Wolf, Max; Bazargan, Ali; Januszewicz, E. Henry; Filshie, Robin; Westerman, David; Seymour, John F.; Tam, Constantine S.
Abstract: Despite its efficacy in prospective trials, full dose fludarabine, cyclophosphamide and rituximab (FCR) may be too toxic for elderly patients with chronic lymphocytic leukemia (CLL) in clinical practice. We retrospectively reviewed the impact of dose reductions in FCR therapy on the outcomes of 42 consecutive patients aged 65–87 (median 72) years. Despite a median cumulative fludarabine dose reduction of 50% from full dose, the objective response and complete response rates were 86% and 38% respectively (frontline 94%/59%; previously treated 80%/24%). Dose reductions of 25–75% were not significantly associated with inferior progression free survival compared to minimal reductions (≤25%) ( p = 0.49), and did not preclude deep responses, including six cases (14%) of minimal residual disease negativity. Although hematological and infectious toxicities were common, treatment limiting adverse effects were infrequent. Dose attenuated FCR appears to have preserved efficacy and may be a viable therapeutic option for elderly patients with CLL.